Eficiencia del Sector Eléctrico Ecuatoriano medida a través del modelo DEA-NETWORK. Período 2012-2021 - Pilco Córdova, Ariel Enrique (2023)
ABSTRAC In a constantly evolving landscape, the electricity sector plays a fundamental role in sustainability and economic progress; The growing demand for energy, combined with the urgency to address environmental challenges, has catapulted the electricity sector into an unprecedented phase of transformation. The Ecuadorian electricity sector includes the phases of: generation, transmission, distribution and sales. Since the change of the Constitution in Ecuador in 2008, the sector has chosen to use a centralized model; The objective of this research is to measure the level of efficiency of the Ecuadorian electricity sector during the period 2012-2021, using a DEA-NETWORK methodology, which allows the examination and integration of each of the previously defined phases, through intermediate inputs. , which are inputs in subsequent phases and outputs of some other phases; These intermediate entries are essential to analyze efficiency from a global overview of the system.For research purposes, the Ecuadorian electricity sector was divided into 9 planning zones; The results revealed that the efficiency of zones 6 and 8 were those that had the greatest impact on the global efficiency of the Ecuadorian Electric Sector during the period 2012-2015. On the other hand, the distribution phase is the most efficient with an index of 0.9605, followed by sales with an index of 0.6251. It is also concluded that the most inefficient phases are generation and transmission, thus verifying the problems caused by the use of a centralized model. Keywords: Efficiency, DEA-NETWORK, Electricity Sector, inputs, outputs, centralized model.